A lithium magnesium nitrogen hydrogen composite material uniformly coated with polymer and preparation method thereof
Through polymer uniform coating technology, the connecting layer and shell layer is formed using dispersants and polymer carriers, the problem of agglomeration and fusion of lithium magnesium nitrogen hydrogen materials during the hydrogen absorption and release cycle is solved, and the stability and efficiency of hydrogen storage capacity is achieved. It is suitable for hydrogen energy transportation and large-scale hydrogen energy storage applications.
Patent Information
- Application Number
- CN202310978748.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-04
AI Technical Summary
Existing lithium-magnesium nitrogen hydrogen materials are prone to agglomeration and fusion during the hydrogen absorption and release cycle, resulting in attenuation of hydrogen storage capacity, making it difficult to meet the needs of hydrogen energy transportation and large-scale hydrogen energy storage.
By uniform coating of polymers, a connecting layer is formed with the surface of lithium magnesium nitrogen hydrogen particles through a dispersant, and a shell layer is formed using a polymer carrier to inhibit the agglomeration and fusion of lithium magnesium nitrogen hydrogen and maintain a small particle size state.
It effectively inhibits the attenuation of the reversible hydrogen storage capacity of lithium-magnesium nitrogen hydrogen materials, improves the performance stability of the material in long-term operation, and maintains a high hydrogen storage capacity, which is suitable for hydrogen energy transportation and large-scale hydrogen energy storage applications.
Smart Images

Figure CN116835526B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium-magnesium-nitrogen-hydrogen composite material uniformly coated with a polymer and a preparation method thereof, and belongs to the field of solid-state hydrogen storage. Background Art
[0002] The safe and efficient storage of hydrogen energy is a key link in the utilization of hydrogen energy. Compared with the more mature high-pressure gaseous hydrogen storage and low-temperature liquid hydrogen storage, solid-state hydrogen storage technology has the advantages of large volume hydrogen storage density, high intrinsic safety, low operating pressure, and low cost of supporting infrastructure equipment. It is very suitable for use in urban areas with dense populations, small spaces and extremely high safety requirements. At present, solid-state hydrogen storage materials are mainly metal and alloy hydrides. For example, the rare earth alloy LaNi5 has a hydrogen storage capacity of 92.3 kg / m at room temperature and 1MPa hydrogen pressure. 3 The volumetric hydrogen storage density is much higher than that of high-pressure gaseous hydrogen storage (40.8 kg / m at 70 MPa). 3 ) and cryogenic liquid hydrogen storage (70.78kg / m 3 ), which has been commercialized in nickel-hydrogen batteries. However, solid-state hydrogen storage materials based on metals and alloys generally have a low mass hydrogen storage density, often in the range of 1.4wt%-2.6wt%, which makes it difficult to meet the requirements of hydrogen energy utilization such as hydrogen energy transportation and large-scale hydrogen energy storage. Therefore, the existing technology has successively developed a series of lightweight composite hydrogen storage materials with a high hydrogen storage capacity of more than 5 wt%, such as NaAlH4, LiBH4, NaBH4, LiNH2-LiH, LiBH4-MgH2, etc., but most of these materials have no reversible cyclability or rapid cyclic decay of hydrogen storage capacity, and hydrogen charging and discharging need to be carried out at high temperatures above 300°C, etc., so they are not commercially applicable. Among this series of lightweight composite hydrogen storage materials, lithium magnesium nitrogen hydride (Li-Mg-NH) has a high hydrogen storage capacity of 5.6 wt%. Theoretically, the hydrogen desorption temperature is as low as 90 °C at a hydrogen pressure of 0.1 MPa (almost the same as the operating conditions of on-board proton exchange membrane fuel cells), and the charging and discharging of hydrogen are completely reversible. Therefore, it is considered to be the next generation solid-state hydrogen storage material with the greatest commercial potential.
[0003] At present, the main preparation method of Li-Mg-NH materials is mechanical ball milling with different molar ratios of Mg(NH2)2 and LiH, or LiNH2 and MgH2. Studies have shown that the particle size of the material plays a crucial role in its hydrogen absorption and desorption properties. By extending the mechanical ball milling time or using high-energy ball milling technology, the particle size of lithium magnesium nitrogen and hydrogen can be reduced to the range of 100 to 200 nanometers. [1], the decrease in particle size can effectively shorten the diffusion distance of the mass transfer process in the solid-phase hydrogen absorption and desorption reaction, and at the same time reduce the reaction kinetic energy barrier. The temperature of Mg(NH2)2-2LiH material fully absorbed and desorbed hydrogen after a short time (such as 3 hours) of ordinary mechanical ball milling is as high as 180℃-200℃, while the temperature of Mg(NH2)2-2LiH material fully absorbed and desorbed hydrogen after a long time (more than 32 hours) of mechanical ball milling can be as low as 130℃. Therefore, nano-sizing Li-Mg-NH by long-term ball milling or high-energy ball milling can effectively improve the operating conditions of the material, allowing it to absorb and desorb hydrogen under milder conditions. However, nano-sized Li-Mg-NH particles usually have higher surface energy, and they are very prone to fusion, agglomeration, regrowth, etc. during the hydrogen absorption and desorption cycle. For example, after the second hydrogenation, the particle size of the Li-Mg-NH material with a particle size range of 100nm-200nm increases from 100nm-200nm to 700nm-800nm, which is the same as the sample after 3 hours of short-term ball milling. The hydrogen absorption and desorption performance also decreases rapidly with the increase of Li-Mg-NH particle size. At present, the reversible hydrogen storage capacity of nano-sized Li-Mg-NH material decays by more than 15% after only a few cycles of hydrogen absorption and desorption, which makes it almost impossible to commercialize. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the present invention provides a lithium-magnesium-nitrogen-hydrogen composite material uniformly coated with a polymer and a preparation method thereof, which inhibits the attenuation of the reversible hydrogen storage capacity of the lithium-magnesium-nitrogen-hydrogen material.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] In a first aspect, the present application provides a method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer, comprising the following steps:
[0007] Preparation of nano-sized lithium magnesium nitrogen hydrogen particles;
[0008] Adding the lithium magnesium nitrogen hydrogen particles and the dispersant containing the electron donor group into the first organic solvent, and mixing them into a dispersed slurry;
[0009] taking a polymer carrier and adding it into a second organic solvent miscible with the first organic solvent to prepare a polymer solution;
[0010] Adding the polymer solution to the dispersed slurry, stirring and then standing for aging to obtain a mixed slurry;
[0011] The aged mixed slurry is separated by centrifugation and dried to obtain the lithium magnesium nitrogen hydrogen composite material uniformly coated with the polymer.
[0012] The present application utilizes polymers to coat lithium-magnesium-nitrogen-hydrogen, thereby suppressing the agglomeration and fusion of lithium-magnesium-nitrogen-hydrogen during hydrogen absorption and desorption, maintaining a small particle size, and being beneficial to suppressing the attenuation of the reversible hydrogen storage capacity of the lithium-magnesium-nitrogen-hydrogen material. The dispersant containing electron donor groups exhibits a high charge density and is easy to form hydrogen bonds with H on the surface of Li-Mg-NH, thereby enhancing the "anchoring" effect of the connecting layer formed by the dispersant on the surface of Li-Mg-NH. In addition, the dispersant can be well combined with the polymer carrier, so that the polymer carrier is uniformly coated on the outermost layer, thereby being able to reduce the content of the polymer carrier, and making the composite material have a higher mass hydrogen storage density.
[0013] Furthermore, the lithium magnesium nitrogen hydrogen particles are a mixture of LiNH2 and MgH2, or a mixture of Mg(NH2)2 and LiH, and the molar ratio of Mg to Li is 1:1-4. Specifically, it can be 1:1, 1:2, 1:3, 1:4, 2:3, 2:5, 2:7, 3:5, 3:7, 3:8, etc.
[0014] Preferably, the molar ratio of Mg to Li in the lithium magnesium nitrogen hydrogen particles is 1:2 or 3:8. The inventors have found that when the Mg-Li molar ratio is 1:2, that is, when the composition contains Mg(NH2)2-2LiH or MgH2-2LiNH2, the composite material exhibits good performance in terms of hydrogen storage capacity and hydrogen absorption and desorption rate.
[0015] Furthermore, the step of preparing nano-sized lithium magnesium nitrogen hydrogen particles comprises:
[0016] Under a protective atmosphere, LiNH2 and MgH2 powders or Mg(NH2)2 and LiH powders are mixed in proportion, and ground with a planetary ball mill for 12h-48h, with a ball-to-material ratio of 20-80 and a rotation speed of 160rpm-300rpm to obtain the nano-sized lithium magnesium nitrogen hydrogen particles.
[0017] Furthermore, in the dispersed slurry, the concentration of the dispersant is 1 mg / ml-25 mg / ml, and the content of the lithium magnesium nitrogen hydrogen particles is 0.1 g / ml-0.85 g / ml; in the polymer solution, the concentration of the polymer carrier is 5 mg / ml-100 mg / ml.
[0018] If the Li-Mg-NH particles are directly coated with a polymer carrier, the polymer carrier is not evenly coated on the surface of the Li-Mg-NH particles, and a higher content of the polymer carrier is required to inhibit the aggregation and fusion of Li-Mg-NH particles. However, the polymer carrier is useless for hydrogen absorption and release, which is equivalent to an impurity. A high content will reduce the mass hydrogen storage density of the composite material. Using an appropriate amount of dispersant adsorbed on the surface of nano-sized Li-Mg-NH particles can reduce the amount of polymer carrier used. The specific reasons are as follows: 1. In the process of forming the dispersed slurry, the dispersant separates the nanoparticles in the solvent from each other and stabilizes the dispersion state, which makes it easier for the polymer carrier added later to uniformly coat the nanoparticles, avoiding the agglomeration of some nanoparticles when no dispersant is added, so that the polymer carrier can only coat the surface of the agglomerate rather than the surface of a single nanoparticle; 2. After adding the polymer carrier, the polymer carrier can interact with the extended chain segments of the dispersant adsorbed on the surface of the Li-Mg-NH particles (such as through π bonds, hydrogen bonds, electrostatic forces, etc.), making the polymer carrier more uniformly coated on the surface of a single nanoparticle and not easy to stack, thereby reducing the amount of polymer carrier used and ensuring that the hydrogen storage capacity of the Li-Mg-NH composite material is >4wt%.
[0019] Furthermore, the step of stirring and then standing for aging comprises:
[0020] Stirring at a speed of 50rpm-200rpm at a temperature of 25℃-50℃ for 1h-3h, and then standing and aging for 1h-24h is more conducive to forming a three-layer structure, with lithium magnesium nitrogen hydrogen as the core, the polymer carrier as the shell, and the dispersant between the two to optimize the combination of the two.
[0021] Furthermore, the step of adding the polymer solution to the dispersed slurry comprises:
[0022] The polymer solution is added to the dispersed slurry at a rate of 1 ml / s-50 ml / s.
[0023] A slower addition speed is beneficial for uniform coating of the polymer on the surface of the dispersant coated with lithium magnesium nitrogen and hydrogen.
[0024] In a second aspect, the present application provides a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer, which includes, from the inside to the outside, a lithium magnesium nitrogen hydrogen core, a connecting layer formed by a dispersant containing an electron donor group, and a shell layer formed by a polymer carrier, wherein the mass of the connecting layer is 1%-5% of the lithium magnesium nitrogen hydrogen core, and the mass of the shell layer is 3%-15% of the lithium magnesium nitrogen hydrogen core;
[0025] The dispersant includes sodium stearate, triethanolammonium stearate, tannic acid, sorbitan trioleate, sorbitan stearate, sorbitan monooleate, sorbitan monostearate, carboxymethyl cellulose, sodium carboxymethyl starch, acrylic acid grafted starch, hydrolyzed acrylonitrile starch, hydrolyzed polyacrylamide, humic acid, acrylic acid polymers, maleic acid polymers, sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, triethanolamine oleate, sodium dibutylbenzene sulfonate, lignin sulfonates, condensed naphthalene sulfonates, sodium polystyrene sulfonate, disodium of higher alcohol phosphatidate, sodium of higher alcohol phosphate diester, sodium dodecyl sulfate, sodium dodecylbenzene sulfate, condensed alkylphenyl ether sulfate, chitosan, aminoalkyl acrylate, hexadecyltrimethylammonium bromide, polyvinylbenzyltrimethylamine salts, dodecylpyridine hydrochloride, hexadecylpyridinium bromide, sodium dodecylaminoacrylate, didodecyldimethyl At least one of ammonium chloride, octadecyl dimethyl betaine, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, chlorinated lignin, lignin, starch, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, propylene glycol methyl ether, dipropylene glycol methyl ether, polyvinyl pyrrolidone, polyvinyl alcohol, polyoxyethylene polyoxypropylene ether, polyvinyl ether, polyacrylamide, polyoxyethylene laurate-2, polyoxyethylene oleate-4, polyoxyethylene lauryl alcohol ether-4, polyoxyethylene nonylphenol ether-9, polyoxyethylene dodecylamine-5, polyoxyethylene octylphenol ether-10, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene dodecylamine-15, polyoxyethylene sorbitan palmitate, polyoxyethylene stearate-30, polyoxyethylene stearate-40, polyoxyethylene sorbitan laurate, polyoxyethylene octylphenol ether-30, and dodecyltrimethylammonium chloride;
[0026] The polymer carrier is selected from one or more of the following, or is a copolymer polymer or block polymer containing the following chain segments: polylactic acid, poly-L-lactic acid, poly-D-lactic acid, poly-racemic lactic acid, polyglycolic acid, polytetrafluoroethylene, polyaniline, polystyrene, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, acrylonitrile-chlorinated polyethylene-styrene copolymer, acrylonitrile-acrylate, styrene copolymer, acrylonitrile-ethylene propylene diene rubber-styrene copolymer, polyethylene, homophenylene polyimide, polyetherimide, polyamideimide, polyvinylidene fluoride, polyvinyl chloride, polystyrene, polymethyl methacrylate, poly(methyl methacrylate) 1-Butyl methacrylate, poly(methyl methacrylate)-co-butyl methacrylate, poly(methyl methacrylate)-butadiene-styrene copolymer, polystyrene-poly(methyl methacrylate) copolymer, polycarbonate, polypropylene, polyparaphenylene, polyetheretherketone, polyetherketone, polyetherketoneketone, polyacetylene, polybutene, poly(4-methyl-1-pentene), poly(dianiline acetylene), polyacrylonitrile, ethyl cellulose, cellulose acetate, cellulose nitrate, elastomer polysiloxane, polycaprolactam, polyhexamethylenediamine adipic anhydride, polyhexamethylenediamine sebacic anhydride, polybutylenediamine sebacic anhydride, polydecanediamine sebacic anhydride, polydodecanediamine dodecanoic anhydride, polydecanediamine dodecanoic anhydride, polyundecamide, polydodecamide, polyoxymethylene, polyphenylene ether, polyphenylene sulfide, polysulfone, polyethersulfone, polyarylsulfone, polyphenylsulfone.
[0027] The shell layer can separate lithium magnesium nitrogen hydrogen, inhibit the agglomeration and fusion of lithium magnesium nitrogen hydrogen during hydrogen absorption and desorption, and inhibit the attenuation of the reversible hydrogen storage capacity of the lithium magnesium nitrogen hydrogen material.
[0028] Furthermore, the mass of the connecting layer is 2%-3 of the lithium magnesium nitrogen hydrogen core, and the thickness is 0.1 μm-1 μm%, which has the best connection effect.
[0029] Furthermore, by virtue of the bonding effect of the connecting layer, the mass of the shell layer is 3%-7% of the lithium magnesium nitrogen hydrogen core, the thickness is 0.1 μm-10 μm, and the dosage is low, which is beneficial to reduce the decrease in the mass hydrogen storage density of the composite material relative to the lithium magnesium nitrogen hydrogen particles.
[0030] The present invention has the beneficial effects that the dispersant can easily form hydrogen bonds with H on the surface of Li-Mg-NH, thereby enhancing the anchoring effect of the connecting layer formed by the dispersant on the surface of Li-Mg-NH, and can also combine the extended chain segments with the polymer carrier, so that the polymer carrier is evenly coated on the outermost layer, and only a small amount of the polymer carrier can be used as the outermost layer of the composite material, so that the composite material has a higher mass hydrogen storage density, and the polymer carrier separates lithium magnesium nitrogen hydrogen, inhibits the agglomeration and fusion of lithium magnesium nitrogen hydrogen during hydrogen absorption and desorption, so that the hydrogen storage capacity of the composite material is relatively stable, and can still maintain a high level after multiple hydrogen absorption and desorption.
[0031] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained by the structures particularly pointed out in the written description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 1 is the XRD spectrum of the product of Example 1 and the nano-sized Li-Mg-NH powder ball-milled in Example 1.
[0033] Figure 2 1 is the XRD spectrum of the product of Example 2 and the nano-sized Li-Mg-NH powder ball-milled in Example 2.
[0034] Figure 3 1 is the XRD spectrum of the product of Example 3 and the nano-sized Li-Mg-NH powder ball-milled in Example 3.
[0035] Figure 4 1 is the hydrogen absorption and desorption cycle curve of the nano-sized Li-Mg-NH powder ball-milled in Example 1.
[0036] Figure 5 This is the hydrogen absorption and desorption cycle curve of the product of Example 1.
[0037] Figure 6 This is the hydrogen absorption and desorption cycle curve of the product of Example 2.
[0038] Figure 7 This is the hydrogen absorption and desorption cycle curve of the product of Example 3. DETAILED DESCRIPTION
[0039] To address the problem of rapid lifetime decay of Li-Mg-NH, the academic community has mainly adopted coating or confinement. The coating method is to use organic substances such as triphenyl phosphate (TPP) [2] 、Poly (4-methyl-1-pentene) (TPX) [3] Acting as a substrate, Li-Mg-NH nanoparticles are coated in it during the ball milling process, so that the organic matter acts as a buffer layer, limiting the contact and fusion of nanoparticles during the organic matter @Li-Mg-NH cycle. The confinement rule is to dissolve the precursors of Mg(NH2)2 and LiH, such as n-butyl magnesium, lithium nitride, etc. in the corresponding solvent and introduce them into the substrate, such as carbon nanofibers or thin hollow carbon spheres, and then heat-treat and reduce them in a hydrogen atmosphere to obtain the substrate @Li-Mg-NH [4-6]These technical means can improve the cycle life of Li-Mg-NH materials to a certain extent, but there are the following defects: (1) The substrate doping amount is too much, and the hydrogen storage capacity of Li-Mg-NH composite materials is less than 3wt%; (2) The synthesis process is complicated, involving complex and costly synthesis processes such as electrospinning, soft / hard template method, heat treatment hydrogenation reduction, and heat treatment amination, which are currently not applied on a large scale. Therefore, considering the hydrogen storage capacity, preparation method and cost, the existing technical means cannot achieve the commercialization of Li-Mg-NH materials.
[0040] In view of the above problems, the present invention provides a method for preparing a polymer-uniformly coated lithium-magnesium-nitrogen-hydrogen composite material, the steps comprising:
[0041] S1: Preparation of nano-sized lithium magnesium nitrogen hydrogen particles.
[0042] S2: adding lithium magnesium nitrogen hydrogen particles and a dispersant containing an electron donor group into a first organic solvent and mixing them into a dispersed slurry.
[0043] S3: taking a polymer carrier and adding it into a second organic solvent that is miscible with the first organic solvent to prepare a polymer solution.
[0044] S4: adding the polymer solution to the dispersed slurry, stirring and then standing for aging to obtain a mixed slurry.
[0045] S5: separating the aged mixed slurry by centrifugation, and drying to obtain a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer.
[0046] The method is simple and cost-effective. The prepared composite material can hinder the agglomeration, fusion and regrowth of nano-Li-Mg-NH particles during the hydrogen absorption and desorption cycle, thereby improving its performance stability in long-term operation and maintaining the high hydrogen storage capacity of the original material.
[0047] The composite material thus prepared includes, from the inside out, a lithium magnesium nitrogen hydrogen core, a connecting layer formed by a dispersant containing an electron donor group, and a shell layer formed by a polymer carrier. The shell layer covers the lithium magnesium nitrogen hydrogen, inhibits the agglomeration and fusion of different lithium magnesium nitrogen hydrogen cores during hydrogen absorption and desorption, is conducive to maintaining the composite material in a small particle size state, and is conducive to inhibiting the attenuation of the reversible hydrogen storage capacity of the lithium magnesium nitrogen hydrogen material. The connecting layer exhibits a high charge density and is easy to form hydrogen bonds with H on the surface of the lithium magnesium nitrogen hydrogen core, thereby enhancing the anchoring effect of the connecting layer on the surface of the lithium magnesium nitrogen hydrogen core. The connecting layer can be well combined with the shell layer, so that the polymer carrier is evenly coated on the outermost layer, thereby being able to reduce the content of the polymer carrier and making the composite material have a higher mass hydrogen storage density.
[0048] Specifically, the lithium magnesium nitrogen hydrogen particles are a mixture of LiNH2 and MgH2, or a mixture of Mg(NH2)2 and LiH. The molar ratio of Mg to Li can be 1:1, 1:2, 1:3, 1:4, 2:3, 2:5, 2:7, 3:5, 3:7, 3:8, etc. The inventors have found that when the Mg-Li molar ratio is close to 1:2, that is, the composition contains Mg(NH2)2-2LiH or MgH2-2LiNH2, the composite material exhibits good performance in terms of hydrogen storage capacity and hydrogen absorption and desorption rate. Therefore, preferably, the molar ratio of Mg to Li in the lithium magnesium nitrogen hydrogen particles is 1:2 or 3:8.
[0049] Dispersants include, but are not limited to, sodium stearate, triethanolammonium stearate, tannic acid, sorbitan trioleate, sorbitan stearate, sorbitan monooleate, sorbitan monostearate, carboxymethyl cellulose, sodium carboxymethyl starch, acrylic acid grafted starch, hydrolyzed acrylonitrile starch, hydrolyzed polyacrylamide, humic acid, acrylic acid polymers, maleic acid polymers, sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, triethanolamine oleate, sodium dibutylbenzene sulfonate, lignin sulfonates, condensed naphthalene sulfonates, sodium polystyrene sulfonate, disodium phosphatidate of higher alcohol, sodium diester of higher alcohol phosphate, sodium dodecyl sulfate, sodium dodecylbenzene sulfate, condensed alkylphenyl ether sulfate, chitosan, aminoalkyl acrylate, hexadecyltrimethylammonium bromide, polyvinylbenzyltrimethylamine salts, dodecylpyridine hydrochloride, hexadecylpyridinium bromide, sodium dodecylaminoacrylate, didodecyl Dimethylammonium chloride, octadecyl dimethyl betaine, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, chlorinated lignin, lignin, starch, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, propylene glycol methyl ether, dipropylene glycol methyl ether, polyvinyl pyrrolidone, polyvinyl alcohol, polyoxyethylene polyoxypropylene ether, polyvinyl ether, polyacrylamide, polyoxyethylene laurate-2, polyoxyethylene oleate-4, polyoxyethylene dodecanol ether-4, polyoxyethylene nonylphenol ether-9, polyoxyethylene dodecylamine-5, polyoxyethylene octylphenol ether-10, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene dodecylamine-15, polyoxyethylene sorbitan palmitate, polyoxyethylene stearate-30, polyoxyethylene stearate-40, polyoxyethylene sorbitan laurate, polyoxyethylene octylphenol ether-30, dodecyltrimethylammonium chloride, etc. The amount of dispersant used should account for 1wt%-5wt% of the mass of the lithium magnesium nitrogen hydrogen core, and the preferred amount should be 2wt%-3wt%. The dispersant forms a connection layer with a thickness of 0.1μm-1μm on the surface of the lithium magnesium nitrogen hydrogen core.
[0050] In the embodiment of the present application, the polymer plays the role of coating the above-mentioned Li-Mg-NH nanoparticles during synthesis. This coating physically isolates the nanoparticles (lithium magnesium nitrogen hydrogen core), inhibits the contact, fusion, agglomeration and regrowth of the nanoparticles during the subsequent long-term operation of hydrogen absorption and desorption of the composite material, and effectively improves the long-term operation stability of the composite material. Taking into account the polymer's H2 solubility and diffusion properties, compatibility with the organic dispersion layer, raw material costs and other factors, the polymer carrier is selected from one or more of the following, or a copolymer polymer or block polymer containing the following segments: polylactic acid (PLA), poly L-lactic acid (PLLA), poly D-lactic acid (PDLA), poly racemic lactic acid (PDLLA), polyglycolic acid (PGA), polytetrafluoroethylene (PTFE), polyaniline (PANI), polystyrene (PS), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-styrene copolymer (AS), butadiene-styrene copolymer (BS), acrylonitrile-styrene-acrylate copolymer (ASA), acrylonitrile-chlorinated polyethylene-styrene copolymer (ACS), acrylonitrile-acrylate copolymer (AAS), acrylonitrile- EPDM (ethylene / propylene / diene)-styrene copolymer (AES), polyethylene (PE), homophenylene polyimide (PI), polyetherimide (PEI), polyamideimide (PAI), polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polystyrene (PS), polymethyl methacrylate (PMMA), poly(methyl methacrylate)-butyl methacrylate (PMMA-co-BM), polymethyl methacrylate-butadiene-styrene copolymer (MBS), polystyrene-polymethyl methacrylate copolymer (MS), polycarbonate (PC), polypropylene (PP), polyparaphenylene (PPP), polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK), polyacetylene (PA), polybutylene (PB), poly(4-methyl-1-pentene) (PMP), poly(diphenylamine) acetylene (PDPA), polyacrylonitrile (PAN), ethyl cellulose (EC), cellulose acetate (CA), cellulose nitrate (CN), elastomer polysiloxane, polycaprolactam (PA6), polyhexamethylenediamine adipic anhydride (PA66), polyhexamethylenediamine sebacic anhydride (PA610), polybutylene diamine sebacic anhydride (PA410), polydecane diamine sebacic anhydride (PA1010), polydodecane diamine dodecanoic anhydride (PA1212), polydecane diamine dodecanoic anhydride (PA1012), polyundecaneamide (PA11), polydodecaneamide (PA12), polyoxymethylene (POM), polyphenylene oxide (PPO), polyphenylene sulfide (PPS), polysulfone (PSF), polyethersulfone (PES), polyarylsulfone (PASF), polyphenylsulfone (PPSU), etc. The molecular weight range is 5000-500000.The total amount of polymer doping should account for 3wt%-15wt% of the mass of the lithium magnesium nitrogen hydrogen core, and the preferred doping amount should be 3wt%-7wt%. The polymer should form hydrogen bonds, π bonds, van der Waals forces and other interactions with the inner connecting layer, and form a shell layer with a thickness of 0.1μm-10μm on the surface of the connecting layer. Most preferably, the concentration of the polymer solution is 0.01g / ml-0.05g / ml.
[0051] Since the Mg-Li composition is sensitive to water and oxygen, an anhydrous organic solvent is required as the solvent. The first organic solvent and the second organic solvent may be the same or different, and are both selected from methanol, ethanol, propanol, isopropanol, butanol, isobutanol, cyclopentanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 4-methylcyclohexanol, glycerol, benzyl alcohol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, methyl ether, ethyl ether, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, tetrahydrofuran, 2-methylfuran, ...1,3-butylene glycol, 1,3-butylene glycol, 1,3-butylene glycol -Methylfuran, 2,5-dimethylfuran, 2-methyltetrahydrofuran, acetone, methylacetone, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylpropionamide, N,N-dimethylacetamide, N-methylpropionamide, N-ethylacetamide, 2-pyrrolidone, N-methylpyrrolidone, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, butylcyclohexane, toluene, xylene, m-xylene, p-xylene, xylene, ethylbenzene, diethylbenzene, dichloromethane, chloroform, carbon tetrachloride.
[0052] Step S1 is specifically as follows: LiNH2 and MgH2 powders or Mg(NH2)2 and LiH powders are mixed in proportion, the mixing can be carried out in a glove box filled with argon, and then ground with a planetary ball mill for 12h-48h, with a ball-to-material ratio of 20-80 and a rotation speed of 160rpm-300rpm to obtain nano-sized lithium magnesium nitrogen hydrogen particles.
[0053] Step S2 is specifically as follows: adding the selected dispersant and a certain amount of lithium magnesium nitrogen hydrogen particles into the corresponding organic solvent, wherein the concentration range of the dispersant in the organic solvent is 1 mg / ml-25 mg / ml, and the amount of lithium magnesium nitrogen hydrogen particles in the organic solvent is 0.1 g / ml-0.85 g / ml. The dispersant needs to form a coating on the Li-Mg-NH nanoparticles under certain conditions, and the mixed solution is magnetically stirred at 100 rpm-600 rpm and reacted at a temperature of 25°C-90°C for 1h-24h to obtain a dispersed slurry.
[0054] Step S3 is specifically as follows: adding the selected polymer carrier to the corresponding organic solvent (the organic solvent may be the same as the solvent in S2, or a different solvent may be used, but the two solvents must be miscible), the concentration range of the polymer carrier in the organic solvent is 5 mg / ml-100 mg / ml, stirring at 100 rpm-600 rpm, 25°C-90°C for 1h-24h, to obtain a clear polymer solution in which the polymer is completely dissolved.
[0055] Step S4 is specifically as follows: adding the polymer solution to the dispersed slurry at a rate of 1 ml / s-50 ml / s, stirring at 50 rpm-200 rpm and 25° C.-50° C. for 1 h-3 h, then stopping stirring and standing for aging for 1 h-24 h.
[0056] Step S5 specifically includes: taking out the aged mixed slurry by centrifugation technology, drying it in a vacuum environment at 25° C.-150° C., removing the organic solvent in the composite material, and obtaining the final product.
[0057] Example 1
[0058] LiNH2 and MgH2 are used as raw materials, polycarbonate (PC) is used as a polymer carrier, polyvinyl pyrrolidone (PVP) is used as a dispersant, and anhydrous tetrahydrofuran (THF) is used as an organic solvent. Among them, the molar ratio of LiNH2 and MgH2 is 2:1; the amount of PC added is 5wt% of the total mass of LiNH2-MgH2; the amount of PVP added is 2wt% of the total mass of LiNH2-MgH2; the concentrations of PC and PVP in anhydrous THF are 12.5mg / ml and 5mg / ml respectively; the amount of LiNH2-MgH2 powder added in anhydrous THF after ball milling is 0.25g / ml.
[0059] The preparation steps are as follows:
[0060] (1) LiNH2 and MgH2 were mixed and mechanically ball-milled at a ball-to-material mass ratio of 60 at a speed of 250 rpm for 30 hours to obtain nano-sized Li-Mg-NH powder. (2) The above-mentioned nano-sized Li-Mg-NH powder and dispersant were added to anhydrous THF at the above-mentioned concentrations and stirred at 400 rpm and 25°C for 1 hour to obtain a uniformly dispersed dispersion slurry A. (3) PC was added to anhydrous THF at the above-mentioned concentrations and stirred at 400 rpm and 50°C for 1 hour to obtain a clear solution B. (4) The clear solution B was added to the dispersed slurry A at a rate of 5 ml / s to obtain a mixed solution C, which was further stirred at 400 rpm and 25°C for 2 hours. (5) The mixed solution C was aged for 12 hours and then centrifuged. The final product was obtained after drying at 70°C under vacuum for 4 hours. The final product was recorded as PC@LMNH-PVP.
[0061] Example 2
[0062] LiNH2 and MgH2 are used as raw materials, poly (4-methyl-1-pentene) (PMP) is used as a polymer carrier, polyvinyl pyrrolidone (PVP) is used as a dispersant, and anhydrous cyclohexane is used as a solvent. Among them, the molar ratio of LiNH2 and MgH2 is 2:1, the amount of PMP added is 5wt% of the total mass of LiNH2-MgH2; the amount of PVP added is 2wt% of the total mass of LiNH2-MgH2; the concentrations of PMP and PVP in anhydrous cyclohexane are 30 mg / ml and 12 mg / ml respectively; the amount of LiNH2-MgH2 powder added in anhydrous THF after ball milling is 0.6g / ml.
[0063] The preparation method is the same as that in Example 1, except that the temperature in steps (3) and (4) is 85°C. The final product is designated as PMP@LMNH-PVP.
[0064] Example 3
[0065] LiNH2 and MgH2 were used as raw materials, polymethyl methacrylate (PMMA) as a polymer carrier, carboxymethyl cellulose (CMC) as a dispersant, and anhydrous tetrahydrofuran (THF) as a solvent. The molar ratio of LiNH2 to MgH2 was 2:1; the amount of PMMA added was 5 wt% of the total mass of LiNH2-MgH2; the amount of CMC added was 5 wt% of the total mass of LiNH2-MgH2; the concentrations of PMMA and CMC in anhydrous THF were 12 mg / ml and 18 mg / ml respectively; the amount of LiNH2-MgH2 powder added in anhydrous THF after ball milling was 0.375 g / ml.
[0066] The preparation method is the same as that in Example 1. The final product is recorded as PMMA@LMNH-CMC.
[0067] The product structures of Example 1, Example 2 and Example 3 and the nano-Li-Mg-NH powders of Example 1, Example 2 and Example 3 that were not mixed with solvent were tested by X-ray diffraction (XRD) technology. The results are shown in Figures 1 to 3 It can be seen that the structure of the final product after wet synthesis is consistent with the structure of the nano-LMNH (lithium magnesium nitrogen hydrogen) powder after mechanical ball milling. The solvent wet synthesis process does not cause the product structure phase change. The final product only contains MgH2 and LiNH2 characteristic peaks, and there are no characteristic peaks of oxides such as MgO, indicating that the synthesis process does not cause oxidation of the product and the process is feasible.
[0068] The products of Example 1, Example 2, and Example 3, as well as the nano-Li-Mg-NH powder of Example 1 that was not mixed with a solvent, were subjected to a cyclic hydrogen absorption and desorption test. The test used a high-temperature and high-pressure gas adsorption instrument (PCT) to perform a cyclic hydrogen absorption and desorption test on the samples. The PCT instrument used was a French Sethram PCT Pro fully automatic Siverts high-pressure gas absorption and desorption analyzer. The test conditions were 180°C, the hydrogen absorption pressure was 80 bar hydrogen pressure, and the hydrogen desorption pressure was 1 bar hydrogen pressure. The products of Example 1, Example 2, and Example 3 were cycled 25 times, and the nano-Li-Mg-NH powder of Example 1 that was not mixed with a solvent was cycled 5 times. The results are shown in the figure. Figures 4 to 7 As shown in the figure, the performance stability of LMNH materials that have only been mechanically ball-milled is poor. After only 5 cycles, its hydrogen desorption capacity drops from 4.4wt% to 3.8wt%, a decay of about 14%. However, by using a dispersant to evenly disperse the nano-LMNH particles (Li-Mg-NH powder) in a certain solvent and adsorbing the dispersant on the surface of the nano-LMNH particles, only a small amount of polymer substrate is used for coating to greatly improve the cyclic stability of the composite material. Under the same test conditions, the hydrogen desorption capacity retention rates of PC@LMNH-PVP, PMP@LMNH-PVP, and PMMA@LMNH-CMC after 25 cycles were 98.8%, 97.8%, and 98.6%, respectively, and the stability was significantly improved compared with that of pure nano-LMNH particles.
[0069] The present application embodiment uses an organic dispersant to be adsorbed on the surface of nano-sized Li-Mg-NH particles. In the process of forming a dispersed slurry, the dispersant separates the nanoparticles in the solvent from each other, stabilizes the dispersed state, and facilitates the polymer carrier added later to uniformly coat the nanoparticles, avoiding the agglomeration of some nanoparticles when no dispersant is added, so that the polymer carrier can only coat the surface of the agglomerate rather than the surface of a single nanoparticle. After adding the polymer carrier, the polymer carrier can interact with the extended chain segment of the dispersant adsorbed on the surface of the Li-Mg-NH particles, so that the polymer carrier is more uniformly coated on the surface of a single nanoparticle and is not easy to stack, thereby reducing the amount of the polymer carrier, ensuring that the hydrogen storage capacity of the Li-Mg-NH composite material is>4wt%. In addition, the present application embodiment does not involve the complex, costly and currently unavailable synthetic processes such as electrostatic spinning, soft / hard template method, heat treatment hydrogenation reduction, heat treatment amination, etc. adopted by the academic community in the preparation of Li-Mg-NH composite materials, and only adopts simple mechanical ball milling and solution configuration means, providing a scalable, cost-controllable, and high-pressure safe synthetic method.
[0070] In the description of this specification, the description with reference to the terms "one embodiment", "certain embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0071] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
[0072] References
[0073] [1]Liu, Y.; Zhong, K.; Luo, K.; Gao, M.; Pan, H.; Wang, QJ Am.Chem. Soc. 2009, 131, 1862.
[0074] [2]Wang, J.; Hu, J.; Liu, Y.; Xiong, Z.; Wu, G.; Pan, H.; Chen, PJMater. Chem. 2009, 19, 2141.
[0075] [3] Cao H, Georgopanos P, Capurso G, Pistidda C, Weigelt F, ChaudharyA, Filiz V, Tseng J, Wharmby M, Dornheim M, Abetz V, Klassen T. Mater. TodayEnergy, 2018, 10, 98.
[0076] [4] Xia, G.; Chen, X.; Zhao, Y.; Li, X.; Guo, Z.; Jensen, C.; Gu, Q.;Yu, X. ACS Appl. Mater. Interfaces 2017, 9, 15502.
[0077] [5]Xia, G.; Tan, Y.; Li, D.; Guo, Z.; Liu, H.; Liu, Z.; Yu, X. Sci.Rep. 2014, 4, 6599.
[0078] [6] Xia, G.; Chen, X.; Zhou, C.; Zhang, C.; Li, D.; Gu, Q.; Guo, Z.; Liu, H.; Liu, Z.; Yu, XJ Mater. Chem. A 2015, 3, 12646.
Claims
1. A method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer, characterized in that: The following steps are involved: Preparation of nano-sized lithium magnesium nitrogen hydrogen particles; Adding the lithium magnesium nitrogen hydrogen particles and the dispersant containing the electron donor group into the first organic solvent, and mixing them into a dispersed slurry; taking a polymer carrier and adding it into a second organic solvent miscible with the first organic solvent to prepare a polymer solution; Adding the polymer solution to the dispersed slurry, stirring and then standing for aging to obtain a mixed slurry; The aged mixed slurry is separated by centrifugation and dried to obtain the lithium magnesium nitrogen hydrogen composite material uniformly coated with the polymer.
2. The method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer according to claim 1, characterized in that: The lithium magnesium nitrogen hydrogen particles are a mixture of LiNH2 and MgH2, or a mixture of Mg(NH2)2 and LiH, and the molar ratio of Mg to Li is 1:1-4.
3. The method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer according to claim 2, characterized in that: The molar ratio of Mg to Li in the lithium magnesium nitrogen hydrogen particles is 1:2 or 3:
8.
4. The method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer according to claim 2, characterized in that: The step of preparing nano-sized lithium magnesium nitrogen hydrogen particles comprises: Under a protective atmosphere, LiNH2 and MgH2 powders or Mg(NH2)2 and LiH powders are mixed in proportion, and ground with a planetary ball mill for 12h-48h, with a ball-to-material ratio of 20-80 and a rotation speed of 160rpm-300rpm to obtain the nano-sized lithium magnesium nitrogen hydrogen particles.
5. The method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer according to claim 1, characterized in that: In the dispersed slurry, the concentration of the dispersant is 1 mg / ml-25 mg / ml, and the content of the lithium magnesium nitrogen hydrogen particles is 0.1 g / ml-0.85 g / ml; in the polymer solution, the concentration of the polymer carrier is 5 mg / ml-100 mg / ml.
6. The method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer according to claim 1, characterized in that: The step of stirring and then standing for aging comprises: The mixture is stirred at a speed of 50 rpm to 200 rpm and a temperature of 25°C to 50°C for 1 h to 3 h, and then allowed to stand for aging for 1 h to 24 h.
7. The method for preparing a lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer according to claim 1, characterized in that: The step of adding the polymer solution to the dispersed slurry comprises: The polymer solution is added to the dispersed slurry at a rate of 1 ml / s-50 ml / s.
8. A lithium magnesium nitrogen hydrogen composite material uniformly coated with a polymer, characterized in that: From the inside out, it includes a lithium magnesium nitrogen hydrogen core, a connecting layer formed by a dispersant containing an electron donor group, and a shell layer formed by a polymer carrier, wherein the mass of the connecting layer is 1%-5% of the lithium magnesium nitrogen hydrogen core, and the mass of the shell layer is 3%-15% of the lithium magnesium nitrogen hydrogen core; The dispersant includes sodium stearate, triethanolammonium stearate, tannic acid, sorbitan trioleate, sorbitan monooleate, sorbitan monostearate, carboxymethyl cellulose, sodium carboxymethyl starch, acrylic acid grafted starch, hydrolyzed acrylonitrile starch, hydrolyzed polyacrylamide, humic acid, acrylic acid polymers, maleic acid polymers, sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, triethanolamine oleate, sodium dibutylbenzene sulfonate, lignin sulfonates, condensed naphthalene sulfonates, sodium polystyrene sulfonate, disodium of higher alcohol phosphatidate, sodium of higher alcohol phosphate diester, sodium dodecyl sulfate, sodium dodecylbenzene sulfate, condensed alkylphenyl ether sulfate, chitosan, aminoalkyl acrylate, hexadecyltrimethylammonium bromide, polyvinylbenzyltrimethylamine salts, dodecylpyridine hydrochloride, hexadecylpyridinium bromide, sodium dodecylaminoacrylate, didodecyldimethylammonium chloride, At least one of octaalkyl dimethyl betaine, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, chlorinated lignin, lignin, starch, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, propylene glycol methyl ether, dipropylene glycol methyl ether, polyvinyl pyrrolidone, polyvinyl alcohol, polyoxyethylene polyoxypropylene ether, polyvinyl ether, polyacrylamide, polyoxyethylene laurate-2, polyoxyethylene oleate-4, polyoxyethylene lauryl alcohol ether-4, polyoxyethylene nonylphenol ether-9, polyoxyethylene dodecylamine-5, polyoxyethylene octylphenol ether-10, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene dodecylamine-15, polyoxyethylene sorbitan palmitate, polyoxyethylene stearate-30, polyoxyethylene stearate-40, polyoxyethylene sorbitan laurate, polyoxyethylene octylphenol ether-30, and dodecyltrimethylammonium chloride; The polymer carrier is selected from one or more of the following, or is a copolymer polymer or a block polymer containing the following chain segments: poly(L-lactic acid), poly(D-lactic acid), poly(racemic lactic acid), polyglycolic acid, polytetrafluoroethylene, polyaniline, polystyrene, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, acrylonitrile-chlorinated polyethylene-styrene copolymer, acrylonitrile-acrylate, styrene copolymer, acrylonitrile-ethylene propylene diene rubber-styrene copolymer, polyethylene, homophenylene polyimide, polyetherimide, polyamideimide, polyvinylidene fluoride, polyvinyl chloride, polystyrene, polymethyl methacrylate, poly(methacrylic acid) methyl ester)-methacrylate-co-butyl ester, polymethyl methacrylate-butadiene-styrene copolymer, polystyrene-polymethyl methacrylate copolymer, polycarbonate, polypropylene, polyparaphenylene, polyetheretherketone, polyetherketone, polyetherketoneketone, polyacetylene, polybutene, poly(4-methyl-1-pentene), polydianilineacetylene, polyacrylonitrile, ethyl cellulose, cellulose acetate, cellulose nitrate, elastomer polysiloxane, polycaprolactam, polyhexamethylenediamine adipic anhydride, polyhexamethylenediamine sebacic anhydride, polybutylenediamine sebacic anhydride, polydecanediamine sebacic anhydride, polydodecanediamine dodecanoic anhydride, polydecanediamine dodecanoic anhydride, polyundecanamide, polydodecaneamide, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polysulfone, polyethersulfone, polyarylsulfone, polyphenylsulfone.
9. The polymer-uniformly coated lithium-magnesium-nitrogen-hydrogen composite material according to claim 8, characterized in that: The mass of the connecting layer is 2%-3% of the lithium magnesium nitrogen hydrogen core, and the thickness is 0.1 μm-1 μm.
10. The polymer-uniformly coated lithium-magnesium-nitrogen-hydrogen composite material according to claim 9, characterized in that: The mass of the shell layer is 3%-7% of the lithium magnesium nitrogen hydrogen core, and the thickness is 0.1 μm-10 μm.
Citation Information
Patent Citations
Method for preparing Li-Mg-N-H hydrogen-storing material
CN101332976A
Light gas-solid hydrogen storage material and preparation method thereof
CN102774809A
Polymer wrapped nano magnesium based hydrogen storage material and preparation method thereof
CN106566965A